Applying The Community-Based Rehabilitation (CBR) to Improve The Quality of Life in Schizophrenia Patients - Kerdsang, Uraiwan; Intarakamhang, Ungsinun; Peungposop, Narisara; Kerdsang, Theerayut (Journal of Behavioral Science for Development, 2022)
Illness with schizophrenia, which is a chronic disease. It is a mental disability that requires continuous treatment and rehabilitation to reduce the disability, stigma, and to create a positive attitude from the people in the community to understand the patients and participate in the rehabilitation and care. Community-based rehabilitation is an important concept that can be used in the rehabilitation of schizophrenia patients. It consists of three integrations: 1) patients, 2) families, and 3) community. These are appropriately linked to each other in health, knowledge, occupation, and social services. The main objective of the CBR project is to improve the patients’ quality of life and independent living. Applied community-based rehabilitation concepts to improve the quality of life of schizophrenic patients. It is a proactive strategy in which community participation based on CBR processes were: 1) situation analysis, 2) plan and design, 3) action and establishment, and 4) monitor and evaluation. The important success factors for CBR consisted of service mind, data return, community participation, knowledge development, leadership, community context, strategy/process, and activities continued. These will provide through improve quality of life, health, progress in remission of symptoms, living with others, feeling like a social part, responsibility, can work, and activity daily living normally. Therefore, CBR is an alternative service that is necessary for improving the quality of life of schizophrenia patients. So, professional providers should be understanding about CBR concept and how to apply it effectively.